Az időskori élelmiszerfogyasztás magyarországi vonatkozásai és időbeli aspektusai - Véghová, Katarína (Jelenkori Társadalmi és Gazdasági Folyamatok, 2012)
Aging is not only a challenge for food producers, but also provides a treasure trove of new opportunities for product development and innovations. We have designed a prototype model of food consumption of the elderly with the goal of calling the attention of producers and growers to the specific needs of this growing market segment. However, the food consumption habits of the elderly cannot be compacted into a single model, since this specific age group is not homogenous. By designing hypothetical models we are hoping to facilitate the further research of the issue. In the near future we want to test and try our general models in practice, involving the producers as well as the consumers. The models point at the specific needs of aging populations and their choice of food products based upon reasonable decisions and focusing on the future. Considerations of the future perspective are an important feature of this behavior, since it might significantly improve the quality of life and health awareness of the elderly, their decisions in the field of consumption, and ultimately their general health and welfare conditions.